Incorporating A Hybrid Fuzzy Logic Model in Diet Style Selection (Global Journal of Sciences, 2025)
The decisions and emotions of people are highly influenced by food pattern which  plays a vital role in their daily activities. Dieting patterns differ in terms of the goals set  by a certain individual. People are advised to know how to regulate their diets and select  eating habits that will promote health by preventing food-related diseases. Six diet  styles were evaluated and ranked by considering multiple important factors utilizing a  multi-criteria decision-making algorithm; the fuzzy Preference Ranking Organization  Method for Enrichment Evaluations (fuzzy PROMETHEE). Of all considered diet  styles, the low-carb diet ranked first diet style with a net flow of 0.2066, and the  intermittent diet ranked sixth with a net flow of -0.3232; however, depending on the  chosen criteria and assigned weights, the outcomes would change dramatically when  weights are modified according to the specific person’s profile. This study will help  individuals, dieticians, and nutritionists make appropriate diet plans by choosing which  pattern to follow with awareness of the probable risk and consequences associated with  their choice.
Keywords: Fuzzy Logic Model; Fuzzy PROMETHEE; Low-carb diet.